Nonstationary processes of acousto-electromagnetic emission of the lithosphere in a seismic active region resulted from surface and borehole measurements - Anh, Nguyen Xuan; N., Uvarov V.; I., Lutsenko V.; V., Popov I.; Luo, Yiyang (Vietnam Journal of Marine Science and Technology, 2017)
The results of synchronous detection of the emission of various components of the electromagnetic and acoustic fields obtained under conditions of low industrial interference and a high level of microseismicity are investigated. To compensate electromagnetic radiation of lithospheric origin, a compensation method was used. The signal loop antenna, recording a mixture of signals of lithospheric and atmospheric-thunderstorm origins, was used as a magnetic core of a steel casing of the borehole. The compensating signal was recorded using an antenna, the receiving coil of which was identical to the coil of the signal antenna. The measurements were carried out in the seismically active region of Russia (the Kamchatka peninsula, the Paratun hydrothermal deposit) at the intersection of the sublatitudinal and submeridional fault zones. Methods for analyzing registration data of non-stationary processes are considered using the example of acoustic-electromagnetic emission of the lithosphere, the electromagnetic component of which is a component of the natural electromagnetic field of the Earth. Their characteristics are estimated and a statistical model is proposed that uses nested semi-Markov processes and finite atomic functions. Observations of geophysical electromagnetic fields, in addition to useful information about the emission processes, contain interference, mainly of technogenic origin. They are especially strong in downhole measurements when a well casing is used as the receiving antenna. These interferences significantly impede the allocation of useful information. The possibility of using bleaching filters to increase the contrast of observation of useful signals of lithospheric origin against their background is considered